Textile Dye Decolorizing Synechococcus PCC7942 Engineered With CotA Laccase - Liang, Yuanmei; Hou, Juan; Liu, Ying; Luo, Yifan; Tang, Jie; Cheng, Jay J.; Daroch, Maurycy (Frontiers in Bioengineering and Biotechnology, 2018)
Cyanobacteria are prokaryotic phototrophs capable of achieving high cellular densities with minimal inputs. These prokaryotic organisms can grow using sunlight as energy source and carbon dioxide as carbon source what makes them promising candidates as microbial cell factories for the production of numerous compounds such as chemicals, fuels, or biocatalysts. In this study, we have successfully designed and constructed using synthetic biology approach two recombinant strains of Synechococcus elongatus PCC7942 for heterologous expression of the industrially relevant Bacillus subtilis CotA laccase. One of the strains (PCC7942-NSI-CotA) was constructed through integration of the laccase gene into neutral site I of the cyanobacterial genome whilst the other (PCC7942-NSII-CotA) targeted neutral site II of the genome. Of the two strains the one with CotA laccase integrated in neutral site II (PCC7942-NSII-CotA) was superior in terms of growth rate and enzymatic activity towards typical laccase substrates: ABTS (2,2ʹ-azino-bis (3-ethylbenzothiazoline-6-sulfonate)) and syringaldazine. That may suggest that two of the traditionally used neutral sites of Synechococcus elongatus PCC7942 are not equally suitable for the expression of certain transgenes. The PCC7942-NSII-CotA produced protein was capable of decolourising three classes of dyes namely: anthraquinonic-, azo- and indigoid-type over seven days of incubation making the strain a potentially useful microbial cell factory for the production of broad-spectrum biodegradation agent. Interestingly, presence of additional synthetic redox mediator ABTS had no effect on the degradation of these dyes.